Relating soil chemical properties to other soil properties and dryland crop production - Sainju, Upendra M.; Liptzin, Daniel (Frontiers in Environmental Science, 2022)
Soil chemical properties have often been related to some other soil properties and crop yields, but extensive evaluation of the relationships of soil chemical properties with other properties and long-term crop yields under dryland cropping systems is lacking. We related six soil chemical properties (pH, electrical conductivity [EC], cation exchange capacity [CEC] and inorganic P [IP], K, and Al concentrations) with 62 other soil physical, chemical, biological, and biochemical properties and crop yields at two long-term (14- and 36-yr old) dryland farming sites in the northern Great Plain, USA. Treatments were rotations of no-tillage and conventional tillage spring wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), pea (Pisum sativum L.), and fallow with or without N fertilization. Soil samples collected to a depth of 0-15 cm in April 2019 were analyzed for soil properties and long-term crop yields were determined. Soil chemical properties were mostly correlated to each other at the short-term than at the long-term site. Based on the principal component analysis, EC, CEC, and IP, and K concentrations were associated with most of the physical, chemical, biological and biochemical properties at both sites. The CEC, IP, and K concentrations were related to mean crop yields across years at individual or combined sites, but other chemical properties were not related to yields. We conclude that CEC, IP, and K concentrations may be used as potential chemical indicators of soil health that were related to most soil properties and crop yields under dryland cropping systems in the semiarid region.